Aspiration development among rural youth : case study Liceo Rural Sámara - Naukkarinen, Hanna (2017)
The aim of this thesis is to provide a preliminary analysis of the aspirations of rural youth in Sámara, Costa Rica and the factors influencing them. This study will supplement the existing literature on aspirations, while providing a new approach to this field. By assessing which factors are most influential to youth’s development of aspirations this study hopes to provide information which can help to improve infrastructure for the development of aspirations in the future. The ultimate goal is to guide future structural changes to promote the development and realization of youth’s aspirations. The study implements an actor-centered approach by utilizing questionnaire data gathered in the target community. The questionnaire data has been analyzed and grouped by many different variables in order to yield the most in depth and accurate findings. The analysis of the data employs the key components of Capacity to Aspire and capital as a guide for analyzing the questionnaire responses. Through the grouping and classification of the data it became clear that further research would be necessary to produce more in depth findings. The current study should be viewed as a preliminary study of aspirations among rural youth. This study validates the findings of previous studies while contributing new insights about the array of factors affecting aspiration development. Most importantly this study brings to light the horizons which young aspirers must face and overcome. A look into what resources should be developed within this rural community in order to foster the development and realization of aspirations is provided through the analysis of the data in this study. Possible avenues for future research which would help in the further development of theory and support for youth aspirations are also described.